A Technology Readiness Level scale for iron and steel industries. (8th August 2016) - Klar, D.; Frishammar, J.; Roman, V.; Hallberg, D.
Abstract : The Technology Readiness Level (TRL) scale is one of the most popular maturity assessment techniques used by industrial firms worldwide. However, it is not a panacea that will work for every firm or every industry in its original form. Consequently, for the scale to be truly useful, it has to be adapted to fit the unique features of different firms and industries. In this article, we propose a revised and domain-specific TRL scale for evaluating technology maturity in iron and steel industries. This revised scale takes into account the idiosyncrasies of such firms, for example, product/process interdependencies, scaling problems, the reliance on pilot and demonstration experiments, and the fact that input and output materials are ingredients rather than components. The revised TRL scale helps managers to assess technology maturity and reduce risk by delivering better project and technology evaluations and providing a 'common language'.